Réponses

Meilleure réponse !
2014-04-29T12:38:19+02:00
Salut; 
A= \frac{11}{3} - \frac{8}{3} x \frac{5}{(-16)} = \frac{11}{3}- \frac{4x2}{3}x \frac{5}{(-4)x4} =  \frac{11}{3} + \frac{2}{3} x \frac{5}{4} =  \frac{44}{12} + \frac{10}{12}=  \frac{54/6}{12/6} = \frac{9}{2}

B= \frac{1- \frac{3}{2}+ \frac{9}{7}  }{ \frac{5}{4}+ \frac{1}{3}  } =  \frac{ \frac{-1}{2} + \frac{9}{7} }{ \frac{11}{12} } =  \frac{ \frac{11}{14} }{ \frac{11}{12} } = \frac{11}{14} x \frac{12}{11} = \frac{6}{7}

C= \frac{2x10^3x5x(10^{-5})^2 }{20} = \frac{2x5}{20} x10^3x(10^{-5})^{2}  = \frac{10}{20}x10 x^{-7} = \frac{1}{2} x10^{-7}

vérifie bien
les x sont des multiplier!
merci , mais je voit pas le C